The role of harvest time and maturity, orchard and simulated wind on postharvest quality of 'Triumph' persimmon fruit and the potential of NIR as non-destructive sorting tool - Zanamwe, Pesanai (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2014.